Challenges of conducting a randomised placebo-controlled trial of spinal surgery: the SUcceSS trial of lumbar spine decompression - Emma Kwan-Yee Ho; Ralph Jasper Mobbs; James Montague van Gelder; Ian Andrew Harris; Gavin Davis; Ralph Stanford; David John Beard; Christopher Gerard Maher; Joanna Prior; Michael Knox; David Barrett Anderson; Rachelle Buchbinder; et al. (Trials, 2023)
Abstract Although placebo-controlled trials are considered the gold standard for evaluating the efficacy of healthcare interventions, they can be perceived to be controversial and challenging to conduct for surgical treatments. The SUcceSS trial is the first placebo-controlled trial of lumbar decompression surgery for symptomatic lumbar canal stenosis. The SUcceSS trial has experienced common issues affecting the implementation of randomised placebo-controlled surgery trials, accentuated by the COVID-19 pandemic. Using the SUcceSS trial as an example, we discuss key challenges and mitigation strategies specific to the conduct of a randomised placebo-controlled surgical trial. Overall, the key lessons learned were (i) involving key stakeholders early and throughout the trial design phase may increase clinician and patient willingness to participate in a placebo-controlled trial of surgical interventions, (ii) additional resources (e.g. budget, staff time) are likely required to successfully operationalise trials of this nature, (iii) the level of placebo fidelity, timing of randomisation relative to intervention delivery, and nuances of the surgical procedure under investigation should be considered carefully. Findings are based on one example of a placebo-controlled surgical trial; however, researchers may benefit from employing or building from the strategies described and lessons learned when designing or implementing future trials of this nature.